Laser diode bars based on AlGaAs/GaAs quantum-well heterostructures with an efficiency up to 70%. (May 2017) - Ladugin, M.A.; Marmalyuk, A.A.; Padalitsa, A.A.; Bagaev, T.A.; Andreev, A.Yu.; Telegin, K.Yu.; Lobintsov, A.V.; Davydova, E.I.; Sapozhnikov, S.M.; Danilov, A.I.; Podkopaev, A.V.; Ivanova, E.B.; et al.
Abstract: The results of the development and fabrication of laser diode bars ( λ = 800 – 810 nm) based on AlGaAs/GaAs quantum-well heterostructures with a high efficiency are presented. An increase in the internal quantum and external differential efficiencies together with a decrease in the working voltage and the series resistance allowed us to improve the output parameters of the semiconductor laser under quasi-cw pumping. The output power of the laser diode bars with a 5-mm transverse length reached 210 W, and the efficiency was ~70%.